Knowledge and Beliefs on Mental Illness among Church Leaders: Basis for Training and Development - Del Rosario, Ma. Camille P.; Lacerna, Clarita; Castaños, Kyle Irvine O.; Fabon, Joseph; Malang, Bernandino P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Mental health awareness and support have become increasingly important worldwide, including in the Philippines. In this context, religious institutions play a crucial role in shaping societal beliefs, attitudes, and approaches to mental illness. This study investigates the knowledge and beliefs about mental illness among church leaders in the Philippines, with a focus on five religious’ denominations: Jehovah’s Witnesses, Baptist, Born Again, Iglesia Ni Cristo, and Roman Catholic. One of the primary objectives of this research was to assess the level of knowledge church leaders possess regarding mental health. The findings indicate that church leaders in the Philippines have a moderate level of knowledge about mental health issues. The mean knowledge score, computed from their responses to a set of Likert-scale questions, falls into the category of "A little." While this level of knowledge may not be extensive, it is a positive starting point for discussions surrounding mental health within religious communities. In terms of beliefs, the respondents exhibited a somewhat agreeable perspective. In conclusion, this study sheds light on the knowledge and beliefs of church leaders in the Philippines regarding mental illness. While they possess a moderate level of knowledge and hold diverse beliefs about the causes and remedies for mental health challenges, their perspectives reflect a nuanced understanding of the complex interplay between religion and mental health. These findings have significant implications for mental health care and support within religious communities and provide a foundation for future research and intervention programs.